2019 AEIT International Conference of Electrical and Electronic Technologies for Automotive (AEIT AUTOMOTIVE) 2019
DOI: 10.23919/eeta.2019.8804527
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle state estimation based on Kalman filters

Abstract: Vehicle state estimation represents a prerequisite for ADAS (Advanced Driver-Assistant Systems) and, more in general, for autonomous driving. In particular, algorithms designed for path or trajectory planning require the continuous knowledge of some data such as the lateral velocity and heading angle of the vehicle, together with its lateral position with respect to the road boundaries. Vehicle state estimation can be assessed by means of extended and unscented Kalman filters (EKF and UKF, respectively), that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Authors in [58] compared performances between EKF and UKF for a similar estimation procedure. Results assess that UKF provides more accurate results, ensuring fast computational time.…”
Section: State Estimationmentioning
confidence: 99%
“…Authors in [58] compared performances between EKF and UKF for a similar estimation procedure. Results assess that UKF provides more accurate results, ensuring fast computational time.…”
Section: State Estimationmentioning
confidence: 99%
“…Unscented Kalman filtering (UKF) overcomes the shortcomings of traditional Kalman filtering and extended Kalman filtering [14]. The sampling points are used to approximate the state distribution without calculating the Jacobian matrix, and the calculation accuracy is higher.…”
Section: Design Of Unscented Kalman Filtering Algorithmmentioning
confidence: 99%
“…This task is implemented using MATLAB programming language on the x86 laptop. Several techniques have been evaluated by the authors as reported in [14], and finally, a UKF algorithm was chosen. In particular, the solution adopted makes use of the road reference frame both for obstacle tracking and ego vehicle state estimation instead of a more traditional Cartesian reference frame on which sensors provide data.…”
Section: Software Architecturementioning
confidence: 99%